A DNA Ligase from a Hyperthermophilic Archaeon with Unique Cofactor Specificity - Nakatani, Masaru (American Society for Microbiology, 2000)
A gene encoding DNA ligase (lig(Tk)) from a hyperthermophilic archaeon, Thermococcus kodakaraensis KOD1, has been cloned and sequenced, and its protein product has been characterized. lig(Tk) consists of 1,686 bp, corresponding to a polypeptide of 562 amino acids with a predicted molecular mass of 64,079 Da. Sequence comparison with previously reported DNA ligases and the presence of conserved motifs suggested that Lig(Tk) was an ATP-dependent DNA ligase. Phylogenetic analysis indicated that Lig(Tk) was closely related to the ATP-dependent DNA ligase from Methanobacterium thermoautotrophicum ΔH, a moderate thermophilic archaeon, along with putative DNA ligases from Euryarchaeota and Crenarchaeota. We expressed lig(Tk) in Escherichia coli and purified the recombinant protein. Recombinant Lig(Tk) was monomeric, as is the case for other DNA ligases. The protein displayed DNA ligase activity in the presence of ATP and Mg(2+). The optimum pH of Lig(Tk) was 8.0, the optimum concentration of Mg(2+), which was indispensable for the enzyme activity, was 14 to 18 mM, and the optimum concentration of K(+) was 10 to 30 mM. Lig(Tk) did not display single-stranded DNA ligase activity. At enzyme concentrations of 200 nM, we observed significant DNA ligase activity even at 100°C. Unexpectedly, Lig(Tk) displayed a relatively small, but significant, DNA ligase activity when NAD(+) was added as the cofactor. Treatment of NAD(+) with hexokinase did not affect this activity, excluding the possibility of contaminant ATP in the NAD(+) solution. This unique cofactor specificity was also supported by the observation of adenylation of Lig(Tk) with NAD(+). This is the first biochemical study of a DNA ligase from a hyperthermophilic archaeon.